PENGARUH PENGETAHUAN KEWIRAUSAHAAN, LINGKUNGAN KELUARGA DAN MOTIVASI BERWIRAUSAHA TERHADAP MINAT MAHASISWA UNTUK BERWIRAUSAHA DI MASA PANDEMI (Studi Kasus Pada Mahasiswa Akuntansi Universitas Islam Malang) - Diyah Ari Manisa; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of study is to determine the effect of entrepreneurial knowledge, family environment and entrepreneurial motivation on student entrepreneurship interest during the pandemic. The population of this research is accounting students class of 2018 and 2019, Faculty of Economics and Business, Islamic University of Malang, and sampling using purposive sampling, the data obtained are 105 respondents. The analytical technique in this study used multiple linear regression analysis with a significance level of 5% with the help of SPSS version 25. Testing the data in this study using methods that include descriptive statistical analysis, validity test, reliability test, normality test, classical assumption test, multiple linear regression analysis, and hypothesis testing (test simultaneous test, coefficient of determination test, partial test). The results of the analysis show that entrepreneurial knowledge, family environment and entrepreneurial motivation simultaneously affect the entrepreneurial interest of students in the accounting study program at the Islamic University of Malang.Keyword : Interest in Entrepreneurship, Knowledge of Entrepreneurship, Family Environment, Entrepreneurial Motivation.